Making a Mint: British Mercantile Influence and the Building of the Japanese Imperial Mint. (2019) - Mizuta, Susumu
Abstract: The Japanese Imperial Mint, which began its operation producing gold and silver coins in Osaka in 1871, has come to represent the self-modernisation of Japanese architecture and society more generally, both in its industrial purpose and western classical style. This article focuses on the planning, construction and socio-spatial design of the mint to resituate the project in the context of British imperial expansion. New archival research in both Japan and Britain, enabling close analysis of overlooked drawings and documents, establishes the Japanese Imperial Mint's dependence on the transfer of men, machinery and plans from the former Hong Kong Mint, mediated and managed by the two firms Glover & Co and Jardine Matheson & Co. This article thus not only sheds new light on these two individually important buildings in colonial and imperial history, and the engineers involved, but illuminates the relationship between British colonial architecture and the activities of British merchants at the edge of empire in East Asia in the nineteenth century.